Valeriana jatamansi Jones ex Roxb. Against Post-Traumatic Stress Disorder, Network Pharmacological Analysis, and In Vivo Evaluation - Yang, Xue; Guo, Jian-You; Jiang, Ya-Ni; Liu, Meng-Meng; Li, Qiu-Yu; Li, Jia-Yuan; Wei, Xiao-Jia; Wan, Guo-Hui; Shi, Jin-Li (Frontiers in Pharmacology, 2021)
Post-traumatic stress disorder (PTSD) is a long-term mental disorder. Zhi zhu xiang (ZZX) which is the root and rhizome of Valeriana jatamansi Jones has been used for anti-anxiety and sedation. Because of PTSD occurring in combination with anxiety and depression, this study aimed at exploring anti-PTSD activity of ZZX and possible mechanisms. Effects 95% ethanol extract of ZZX on behavior of PTSD mice induced by single prolonged stress & foot-shock were evaluated by open field test (OFT), elevated plus maze (EPM), force swimming test (FST) and fear conditioning response (FCR). Potentially active components, targets and pathways of ZZX involved in PTSD were analyzed by network pharmacology and molecular docking. Enzyme-linked immunosorbent assay was used to detect levels of neurotransmitters, including 5-hydroxytryptamine (5-HT), norepinephrine (NE), dopamine (DA), and γ-aminobutyric acid (GABA) and glutamic acid (Glu) in the hippocampus, as well as the levels of adrenocorticotropic hormone (ACTH), corticosterone (CORT) and corticotropin releasing hormone (CRH) in the hypothalamic pituitary adrenal (HPA) axis of serum. Levels of cannabinoid receptor1 (CB1), diacylglycerol lipase α (DAGLα), monoacylglycerol lipase (MAGL) and fatty acid amide hydrolase (FAAH) mRNA in the hippocampus were detected by real-time PCR. The results showed that ZZX (80 mg·kg-1, ZZX-M) increased PTSD mice' movement distance, residence time and frequency of exploring in the central area of OFT and the open arm of EPM, and reduced the immobility time of mice in the FST and the freezing time of mice in the FCR. Results of network pharmacology and molecular docking showed that 47 potentially active compounds of ZZX exerted an anti-PTSD effect by acting on key targets, including CNR1(same as CB1), MAOA, NR3C1, MAPK14, MAPK8, HTR2C, DRD2 through multiple signaling pathways such as serotonergic, dopaminergic, glutamatergic and retrograde endocannabinoid signaling. The experimental results showed that ZZX-M restored levels of 5-HT, NE, DA, GABA, Glu in the hippocampus and ACTH, CORT, CRH in serum. Meanwhile, ZZX-M up-regulated levels of CB1 and DAGLα genes, but down-regulated levels of MAGL and FAAH genes in the hippocampus. This study demonstrates that ZZX alleviates PTSD-like behavior in mice by restoring neurotransmitters and HPA axis and regulating endocannabinoid related genes.